Characterization of the surface protein layers of the mosquito-pathogenic strains of Bacillus sphaericus. - Lewis, L O (1987)
The protein surface layers on the cell walls of mosquito-pathogenic and nonpathogenic Bacillus sphaericus strains were studied by structural, biochemical, and serological methods. The surface structure of two representative insect-pathogenic strains had the form of a delicate linear array with a repeat interval of 5 nm. This was distinctly different from the tetragonal array of the P-1 strain in spacing and arrangement. The surface layers were composed of acidic glycoproteins with molecular weights ranging from approximately 133,000 to 155,000. Peptide mapping and serological analysis of the surface proteins revealed eight distinct groups among the pathogens. These groups were very similar to the groupings determined by flagellar-antigen serotyping and bacteriophage typing.